Manajemen Badan Usaha Milik Desa (BUMDes) dalamUpayaMemulihkan Pendapatan Asli Desa (PADes) di Era NewNormal (Studi Kasus BUMDes Tirta Mandiri Desa Ponggok Kecamatan PolanharjoKabupaten Klaten) - Putri Aryawati Widya Budi; Dyah Hariani; Augustin Rina Herawati (Journal of Public Policy and Management Review, 2022)
Village Owned Enterprises (BUMDes) are one of the village economic institutions that have a role in increasing Village Original Income (PADes). The problemfaced by TirtaMandiri BUMDes is the decline in income from existing business units which are a result of the Covid-19 pandemic.The purpose of this study was to analyze the management of BUMDes Tirta Mandiri in an ef ort to restore Village Original Income in the newnormal era and analyze the supporting and inhibiting factors. This research uses descriptivequalitative research methods, data collection techniques through interviews, observations, and documentation. The results showed that BUMDes planning is not mature enoughandhas not thought about long-term plans. In organizing, the division of labor is not according to expertise and there is still a lack of emphasis on job descriptions. Thedirective function has not been carried out thoroughly to all employees. Inthesupervisory function, the assessment has not been adjusted to the CHSE (Cleanliness, Health, Safety, Environment) program. Supporting factors are namely the existence of village potential, collaboration with other parties, and government commitment. Whilethe inhibiting factors are human resources management and budget constraints